جهود عبد الحميد مهري السياسية لنصرة القضية الجزائرية بالخارج 1954-1962 - العبد, صبرة (My University, 2021)
سأحاول في هذا المقال الحديث عن شخصية المناضل الراحل عبد الحميد مهري وتوجهاته الوطنية والقومية، ودوره الفعال في دعم القضية الجزائرية و الوحدة المغاربية خاصة في الفترة الممتدة بين 1954-1962 بإعتبارها أهم وأحرج السنوات في رحلة تقرير المصير. إذ تناولت المحاور الأساسية للموضوع بدءا بنشاطه السياسي في تونس ثم جهوده في نصرة القضية الجزائرية من خلال الدعم اللوجستيكي والدبلوماسي بدمشق، بالإضافة إلى الدور الفعال الذي قام به في الحكومة المؤقتة وعلاقاته مع زعماء الحركات الوطنية المغاربية بهدف خلق قواعد خلفية غرب القارة الآسياوية للإمداد الثورة الجزائرية ونصرة قضيتها العادلة. ليصبح بذلك مثالا يحتذى به في النضال القومي والتحرري . In this article, I will try to talk about the personality of the late militant Abdelhamid Mehri, his patriotic and nationalist tendencies, and his effective role in supporting the Algerian cause and Maghreb unity, especially during the period from 1954 to 1962, as being the most important and embarrassing years in the journey of self-determination. The study discussed such key axes as Mehri’s political activity in Tunisia, his efforts to support the Algerian cause through logistical and diplomatic support in Damascus, in addition to the effective role he played in the interim government and his relations with the leaders of the national Maghreb movements with the aim of creating background bases in the West of the Asian continent to supply the Algerian revolution with necessary material and support its fair cause. Mehri’s endeavours made of him an ideal example to follow in the national and liberation struggle.
مقال
Keywords: عبد الحميد مهري؛ القضية الجزائرية؛ الدعم الدبلوماسي؛ الخارجي؛ لجنة التنسيق.